2004
DOI: 10.1083/jcb.200402046
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix mineralization is regulated locally; different roles of two gla-containing proteins

Abstract: Extracellular matrix mineralization (ECMM) is a physiologic process in the skeleton and in teeth and a pathologic one in other organs. The molecular mechanisms controlling ECMM are poorly understood. Inactivation of Matrix gla protein (Mgp) revealed that MGP is an inhibitor of ECMM. The fact that MGP is present in the general circulation raises the question of whether ECMM is regulated locally and/or systemically. Here, we show that restoration of Mgp expression in arteries rescues the arterial mineralization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
348
2
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(378 citation statements)
references
References 29 publications
14
348
2
14
Order By: Relevance
“…Indication that such transformations could take place in the aortic wall has been provided by Watson et al (11) who showed that a subpopulation of cultured VSMCs were transformed to calcifying vascular cells (CVCs) capable of forming a mineralized matrix. We have shown (12) that BMP-2 and MGP are both synthesized by VSMCs and Murshed et al (13) have shown that MGP synthesized in the vessel wall and not blood born MGP is the in vivo pool of the protein that is active as the vascular calcification inhibitor. These findings emphasize the importance to understand the MGP-BMP-2 interaction in inhibition of vascular calcification.…”
mentioning
confidence: 74%
“…Indication that such transformations could take place in the aortic wall has been provided by Watson et al (11) who showed that a subpopulation of cultured VSMCs were transformed to calcifying vascular cells (CVCs) capable of forming a mineralized matrix. We have shown (12) that BMP-2 and MGP are both synthesized by VSMCs and Murshed et al (13) have shown that MGP synthesized in the vessel wall and not blood born MGP is the in vivo pool of the protein that is active as the vascular calcification inhibitor. These findings emphasize the importance to understand the MGP-BMP-2 interaction in inhibition of vascular calcification.…”
mentioning
confidence: 74%
“…The ank/ank mice failed to thrive. 3,8,11,12 However, there was no significant difference in body weight of 10 male mice of each geno- Figure 7. Correction of increased calcification of ank/ank aortic ring explants and cultured SMCs by Vanin-1 gene knockout.…”
Section: Vanin-1 Knockout Does Not Suppress Calcification By Ank/ankmentioning
confidence: 99%
“…[1][2][3][4] Heritable deficiencies in mineralization regulators have been particularly informative about hierarchical, co-operative, and antagonistic relationships among such factors. 2,5,6 Indeed, the particularly potent capacity of PP i to inhibit hydroxyapatite crystal growth 7 has been underscored by the phenotypic effects of alteration of PP i transport and generation.…”
mentioning
confidence: 99%
“…In the vascular wall, the inhibition of γ-carboxylation of Glu residues yielded the undercarboxylation of MGP and the subsequent calcification of the tunica media [10]. Moreover, it has been shown in the bone tissue of transgenic mice, which produced two distinct mutated forms of MGP in osteoblasts, that the Gla residues are required for MGP antimineralization function [21].…”
Section: Discussionmentioning
confidence: 99%